PERBAIKAN KERUSAKAN SUPERVISION B PADA AMSC MEREK ELSA DI PERUM LPPNPI CABANG DENPASAR - Dewi Dasi, Ni Nyoman Madhawi Dewi Dasi (Cipta Kind Publisher, 2023)
Automatic Message Switching Center (AMSC) is an equipment that can receive, process and send aviation news according to the general format used for aeronautical purposes. AMSC is a tool for distributing computerized news as regulated in ICAO Annex 10 Volume II for the AFTN (Aeronautical Fixed Telecommunication Network) network. AFTN is the network used by AMSC for flight data communications between one airport and another. Flight data communication is very important because it is useful for sending flight schedules, weather news, NOTAMs, or other news related to flights. Perum LPPNPI Denpasar Branch uses AMSC brand ELSA AROMES – 1003Qi which has 64 channels. AMSC uses a Dual System to avoid down conditions in the system. Messages entering the AMSC will be corrected by the Supervision module, apart from that, this unit can send or receive news from/to the system. This unit is connected via a LAN network to the AMSC system MPU and via RS-232 serial to the signal selector. Keywords: AMSC, Automatic Message Switching Center, AFTN, ELSA AMSC, AROMES-1003Qi, Supervision AMSC, AirNav Denpasar